2013
DOI: 10.1002/prot.24460
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of HIV‐1 RT‐DNA‐nevirapine complexes explains NNRTI inhibition and resistance by connection mutations

Abstract: HIV-1 reverse transcriptase (RT) is a multifunctional enzyme that is targeted by nucleoside analogs (NRTIs) and nonnucleoside inhibitors (NNRTIs). NNRTIs are allosteric inhibitors of RT, and constitute an integral part of the highly active antiretroviral therapy (HAART) regimen. Under selective pressure, HIV-1 acquires resistance against NNRTIs primarily by selecting mutations around the NNRTI pocket. Complete RT sequencing of clinical isolates revealed that spatially distal mutations arising in connection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…However, it is clear from our studies that when associated with RNA/DNA complexes, the combination of mutations N348I and T369I has a major impact in the RNase H activity of the RT. These results are also in agreement with the notion that a number of distal connection subdomain mutations contribute to drug resistance by altering the dynamic properties of the RT and contact networks involving amino acid residues in the viral enzyme, identified by using molecular dynamics ( 51 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, it is clear from our studies that when associated with RNA/DNA complexes, the combination of mutations N348I and T369I has a major impact in the RNase H activity of the RT. These results are also in agreement with the notion that a number of distal connection subdomain mutations contribute to drug resistance by altering the dynamic properties of the RT and contact networks involving amino acid residues in the viral enzyme, identified by using molecular dynamics ( 51 ).…”
Section: Discussionsupporting
confidence: 88%
“…Unlike mutations analyzed in our study whose prevalence in untreated patients is lower than 7.5%, A400T is a common polymorphism in HIV-1 group M isolates with a prevalence of nearly 56% in untreated patients. Modeling studies have shown little differences between ternary complexes containing the WT or the double-mutant N348I/T369I RT, associated with a DNA/DNA template-primer and nevirapine ( 51 ). However, it is clear from our studies that when associated with RNA/DNA complexes, the combination of mutations N348I and T369I has a major impact in the RNase H activity of the RT.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the N348I mutation increases the processivity of RT and enhances NVP dissociation from the NNIBP [ 38 ]. A molecular dynamics modeling study proposes that N348I contributes to NVP resistance through a long-range allosteric communication network between the connection and NNIBP [ 140 ]. More recently, Brehm et al [ 138 ] reported the presence of the N348I mutation in HIV-1C patients who failed d4T/3TC/NVP or d4T/3TC/EFV therapy.…”
Section: Resistance To Antiretroviral Therapies Among Different Himentioning
confidence: 99%
“…Received 12 August 2014, revised 3 December 2014 and accepted for publication 6 December 2014 Acquired immune deficiency syndrome (AIDS) is mainly caused by HIV-1 infection and remains a global problem for human health (1). Almost half of the FDA-approved anti-HIV drugs target HIV-1 RT, which is a pivotal multifunctional enzyme in the replicative cycle of HIV-1 (2). The success of highly active antiretroviral therapy (HAART) regimens has significantly reduced the morbidity and mortality of HIV-infected individuals (1,(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The success of highly active antiretroviral therapy (HAART) regimens has significantly reduced the morbidity and mortality of HIV‐infected individuals . Non‐nucleoside reverse transcriptase inhibitors (NNRTIs) are important and frequently clinical used components in HAART regimen for HIV‐1 infections .…”
mentioning
confidence: 99%